MiRNA-21 Expression Decreases from Primary Tumors to Liver Metastases in Colorectal Carcinoma - Feiersinger, Fabian; Nolte, Elke; Wach, Sven; Rau, Tilman; Vassos, Nikolaos; Geppert, Carol-Immanuel; Konrad, Andreas; Merkel, Susanne; Taubert, Helge; Stürzl, Michael; Croner, Roland S. (PLoS ONE, 2016)
Metastasis is the major cause of death in colorectal cancer patients. Expression of certain miRNAs in the primary tumors has been shown to be associated with progression of colorectal cancer and the initiation of metastasis. In this study, we compared miRNA expression in primary colorectal cancer and corresponding liver metastases in order to get an idea of the oncogenic importance of the miRNAs in established metastases.We analyzed the expression of miRNA-21, miRNA-31 and miRNA-373 in corresponding formalin-fixed paraffin-embedded (FFPE) tissue samples of primary colorectal cancer, liver metastasis and healthy tissues of 29 patients by quantitative real-time PCR.All three miRNAs were significantly up-regulated in the primary tumor tissues as compared to healthy colon mucosa of the respective patients (p < 0.01). MiRNA-21 and miRNA-31 were also higher expressed in liver metastases as compared to healthy liver tissues (p < 0.01). No significant difference of expression of miRNA-31 and miRNA-373 was observed between primary tumors and metastases. Of note, miRNA-21 expression was significantly reduced in liver metastases as compared to the primary colorectal tumors (p < 0.01).In the context of previous studies demonstrating increased miRNA-21 expression in metastatic primary tumors, our findings raise the question whether miRNA-21 might be involved in the initiation but not in the perpetuation and growth of metastases.
EVALuna2:6831